Structural changes in cell wall of Japanese radish accompanied by release of rhamnogalacturonan during pressure cooker heating. (1st July 2021) - Tsuchida, Mitose; Yamaguchi, Hideyuki; Katayama, Norihisa; Sato, Yoko; Kawashima, Wakano; Kasai, Midori
Highlights: Cell wall of heated Japanese radish between 100 °C and 117 °C were compared. Eluted components from AIS of raw samples heated in water were analyzed. 13 C CP/MAS NMR couldn't discriminate between temperatures of AIS from heated samples. PST/MAS NMR showed clear signal changes in side chain of RG depending on temperature. Heating radish at 117 °C for 3 h caused loosening of cell wall with keeping its shape. Abstract: Changes in the cell wall of Japanese radish due to heating at 100 °C or 117 °C for 3 h were examined. Signals in 13 C cross polarization magic angle spinning solid-state NMR (which detects rigid components) showed no differences between heating temperatures. 13 C pulse saturation transfer magic angle spinning NMR (which detects flexible components) showed clear temperature-dependent changes in the rhamnose side chains of rhamnogalacturonan. Alcohol-insoluble solids isolated from raw samples were heated in water at 100 °C or 117 °C for 3 h. The concentrations of dissolved sugars and metal ions measured after heating in water at 117 °C were greater than in samples heated at 100 °C, indicating that loosening of cell wall structures increased with temperature, likely via degradation and elution of rhamnogalacturonan followed by β-elimination of homogalacturonan, and fewer interactions between cell wall components, including divalent metal ions. Vegetable shape was retained despite fewer interactions.